Characterization of the demand for graduates from different state higher education programs in the context of the automation of production processes (Industry 4.0). - Ruiz Mejías, Keynor (2025)
This paper aims to characterize the labor demand of graduates of state universities in Costa Rica, in the context of the automation of certain processes and tasks. The subject of study was Data obtained from a survey made for graduates between 2013-2016, generated by the National Council of Rectors. The performance desired by the employer vs. actual performance was analyzed; likewise, activities were classified according to the probability or susceptibility to automation, as identified in the literature review. Among the main findings is that the most repetitive and routine tasks are classified with greater potential for automation. There are certain gaps between what is important to an employer and the actual performance of the graduate, such as, for example, the use of time and the handling of a second language (in this case, English). Considering digital and automation as a necessary component to strengthen the curricula in higher education, as well as to provide people with the skills and knowledge that will enable them to face a more digitalized and occupationally flexible labor market daily.